Conflict Narratives from the Health Care Frontline: A Conceptual Model. (1st February 2016) - Kim, Sara; Buttrick, Elizabeth; Bohannon, Isaac; Fehr, Ryan; Frans, Elise; Shannon, Sarah E.
Abstract: We examined health care conflicts through interviews with health care leaders, providers, and patients. Ninety‐two medical providers, nurses, technologists, hospital leaders, and patients/families shared 156 conflict stories. We identified individual, interpersonal, and organizational factors contributing to interprofessional conflicts. Individual contributors included resource depletion (i.e., stress and fatigue), perceptions of others' seemingly selfish motives, and judgment toward colleagues' competence. Interpersonal conflicts involved prior unresolved conflicts, dehumanization, power differentials, or communication breakdown. Organizational factors included navigating within complex organizational structures and noncompliance with group norms. Conflicts resulted in negative consequences for patients (safety, satisfaction), providers (career, relationships, satisfaction, morale), and organizations (performance, staff turnover).